Explaining the patterns of contacts between interest groups and political parties: Revising the standard model for populist times. (May 2021) - Berkhout, Joost; Hanegraaff, Marcel; Statsch, Patrick
Why do some groups and parties maintain contact whereas others do not? Recent studies explain party–interest group contact on the basis of power and ideological proximity. This 'standard' model provides reasonably good explanations for the general patterns of party–interest group interactions but requires specification to account for the profound political changes caused by the rise of populist parties. Our argument is (a) that populist ideology leads interest groups to have relatively infrequent contact with populist parties and (b) that strategic incentives related to populist parties moderate the effects of power and proximity. We examine the contact patterns of over 1600 interest groups and political parties derived from elite survey data from five European countries. We find empirical support for our arguments and relate these to normative concerns about the selective involvement of parties and groups in policymaking.